Enhancing chemosensitivity of PANC1 pancreatic cancer cells to gemcitabine using ANGTPL4, Notch1 and NF-κβ1 siRNAs - Abdulfattah Al-Kadash; Walhan Alshaer; Ismail Sami Mahmoud; Suha Wehaibi; Malek Zihlif (Future Science OA, 2024)
Aim: siRNA can silence targeted genes with lesser toxicity than therapeutic drugs. Therefore, this study aims to investigate new approaches to treat pancreatic cancer (PC) using combinations of siRNA and gemcitabine. Methods: Three genes, ANGTPL4, Notch1 and NF-κβ1, were silenced using siRNA, and their anti-proliferative effects were studied in combination with gemcitabine on pancreatic cancer cell line (PANC-1) using MTT viability assay. Results: Our results showed a significant reduction in PANC-1 cells growth upon treating cells with gemcitabine and single and combinations of siRNA sequences specific for ANGTPL4, Notch1 and NF-κβ1 genes. Conclusion: Co-transfection of gemcitabine-treated PANC-1 cells with ANGPTL4, Notch1 and NF-κβsiRNAs enhances the chemosensitivity of PANC-1 cells to gemcitabine can be a promising therapeutic approach.